1998
DOI: 10.1136/pgmj.74.868.89
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional learning

Abstract: SummaryEffective care in hospitals and in the community requires doctors, nurses and other healthcare professionals to work together to achieve the best possible outcomes for patients. In the UK, a shift in emphasis towards a primary care led service and recent changes to the ways in which healthcare is funded and organised, are profoundly affecting traditional patterns of working. Boundaries which define the roles and responsibilities of individual professions are becoming less clear and there is increasing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
92
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(97 citation statements)
references
References 7 publications
4
92
0
1
Order By: Relevance
“…Pride in their profession came with the realisation of the importance of their own role 16 . Students valued gaining knowledge about the roles of the different professions as these roles were often unclear in the team 19 . Improved knowledge of team members' roles and responsibilities also tend to have positive effects on the patient's treatment 16 and the student's clinical experience 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Pride in their profession came with the realisation of the importance of their own role 16 . Students valued gaining knowledge about the roles of the different professions as these roles were often unclear in the team 19 . Improved knowledge of team members' roles and responsibilities also tend to have positive effects on the patient's treatment 16 and the student's clinical experience 20 .…”
Section: Discussionmentioning
confidence: 99%
“…According to Molander (1993), practical real-world examples are the most valuable for acquiring different types of knowledge. Students rate IPL favourably when they see that the experience they gain in their practice placements is of immediate relevance to their future professional practice (Parsell & Bligh, 1998).…”
Section: Interprofessional Collaborative Learning and Competencementioning
confidence: 99%
“…In this study, patients took part in the interprofessional collaborative teamwork and all patient interactions were real, which according to Molander (1993) and Parsell & Bligh (1998) is important for learning. Earlier studies have shown that student motivation for interprofessional collaboration appears to be strengthened by IPL through practice-based shadowing (Fougner & Hortvedt 2013, Lindqvist 2005).…”
Section: The Need For An Interprofessional Approachmentioning
confidence: 99%
“…Although there are issues that cause barriers to interprofessional learning at the pre-licensure level, such as basic differences in curriculum structures, lack of support, lack of comfort in teaching across disciplines, and financial constraints [26], one of the major difficulties is a clear understanding of what competencies should be emphasized and measured in an undergraduate interprofessional curriculum [7]. Certainly, competencies are often used within specific professions to create standards within the profession [27,13]; however, interprofessional competencies have been difficult to agree upon across disciplines and practice settings.…”
Section: Introductionmentioning
confidence: 99%